Buck converter controlled with ZAD and FPIC for DC-DC signal regulation - Fredy E. Hoyos Velasco; Yeison Alberto Garcés Gómez; John E. Candelo-Becerra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents the performance of a fixed-point induction control (FPIC) technique working in conjunction with the non-linear control technique called zero average dynamics (ZAD) to control chaos in a buck converter. The control technique consists of a sliding surface in which the error tends to zero at each sampling period. A switch is controlled by using centered pulse width modulation (CPWM) control signal. The converter controlled with ZAD-FPIC has been simulated in Matlab and implemented using rapid control prototyping (RCP) in a DSP to make comparisons between simulation and experimental tests. To perform this comparison, some variations in the control parameter and the voltage reference are made in order to evaluate the performance of the system. Results are obtained with errors lower than 1 % which demonstrates the good performance of the control techniques.